Insights from the scale-up and implementation of the Deadly Liver Mob program across nine sites in New South Wales, Australia, according to the RE-AIM framework - Elena Cama; Kim Beadman; Mitch Beadman; Melinda Walker; Carla Treloar (BMC, 2023)
Abstract Background The Deadly Liver Mob (DLM) program is a peer-led health promotion program that aims to improve access to screening and treatment for blood borne viruses and sexually transmissible infections for Aboriginal and Torres Strait Islander Australians. In this paper, we used client and staff insights to explore the successes and challenges of implementing the DLM program according to the RE-AIM framework, which explores real-world implementation of interventions according to reach, effectiveness, adoption, implementation, and maintenance. Methods Clients and staff were recruited through the DLM program. Semi-structured interviews were conducted with four Aboriginal and Torres Strait Islander and 11 non-Aboriginal or Torres Strait Islander health workers, as well as 33 Aboriginal and Torres Strait Islander clients of the program. Results Findings show the positive effects of the DLM program, in creating a culturally safe and sensitive environment for Aboriginal and Torres Strait Islander clients to access care. In particular, the employment of frontline Aboriginal and Torres Strait Islander workers to deliver the education was touted as one of the primary successes of the program, in enabling workers to build trust between clients and mainstream health systems, which has the flow on effect of encouraging clients to go through to screening. The use of the RE-AIM framework illustrates the challenges of implementing real-world interventions across various locations, such as the difficulties in delivering DLM in regional and remote areas due to covering large geographic areas with minimal public transport available. Conclusions The data emphasise the need for interventions to be adaptable and flexible, altering elements of the program to suit local and community needs, such as by offering mobile and outreach services to enable access across regional and rural areas. The findings of this evaluation have been used to develop tools so that the learnings from DLM can be shared with others who may be hoping to implement DLM or other similar programs.